Design and Development of a Wireless Lamp Charging System - Engr. Ajayi-Smart Emmanuel Abiodun (Journal of Power Electronics and Devices, 2017)
Wireless is a technology of transmitting power through an air gap to electrical devices for the purpose of energy replenishment. The recent progress in wireless charging techniques and development of commercial products has provided a promising alternative way to address the energy tailback of unadventurously portable-power devices. This work is an innovative application of Faraday’s laws of electromagnetic induction. A charging station sends energy through inductive coupling to an electrical device, which stores the energy in the batteries. Because there is a small gap between the two coils, inductive charging is one kind of short-distance wireless energy transfer. Induction coils are attached to transmitter and the portable device, so that the device receives power from the electromagnetic field created by the transmitting unit and stores the energy in the battery.